PENGARUH PAJAK BUMI DAN BANGUNAN (PBB) DAN BEA PEROLEHAN HAK ATAS TANAH BANGUNAN (BPHTB) TERHADAP PAJAK DAERAH KABUPATEN BUNGO - Widya Pratiwi; Ariyanto M; Eva Marlina Marlina (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
Since 1 January 2011 the management of the UN and BPHTB has become the full responsibility and authority of the regional government. This is in accordance with the mandate of Law Number 28 of 2009 dated 15 September 2009 concerning Regional Taxes and Regional Retribution, the authority to collect the United Nations and the BPHTB was handed over to the Regency / City Government. Because the UN and BPHTB have become the responsibility of the region, of course this type of tax is also included as one source of Local Revenue (PAD) which of course is part of the tax and in accordance with the tax function as a budget. The purpose of this study is to see how much influence the UN and BPHTB partially or jointly on Regional Taxes. The analytical tool for this study uses multiple regression analysis. The results of the research prove that the PBB and BPHTB partially or jointly affect the Regional Tax.